High‐sensitivity chemiluminescent immunoassay investigation and application for the detection of T‐2 toxin and major metabolite HT‐2 toxin. (16th June 2016) - Li, Yanshen; Zhang, Jing; Mao, Xin; Wu, Yongtao; Liu, Gongzhen; Song, Liting; Li, Yonggang; Yang, Jianrong; You, Yanli; Cao, Xuelin
Abstract: BACKGROUND: T‐2 toxin is a widely distributed mycotoxin in cereals. HT‐2 toxin is the major metabolite, which is also a contaminant in cereals. T‐2 toxin and HT‐2 toxin have been identified as having carcinogenic, hepatotoxic, teratogenic and immunotoxic properties. To reduce the risk of contamination, a rapid, highly sensitive and inexpensive assay for the detection is required. RESULTS: In this study a high‐sensitivity chemiluminescent enzyme‐linked immunoassay (CL‐ELISA) of T‐2 toxin and HT‐2 toxin was developed. With the help of the chemiluminescent substrate, this protocol showed a highly sensitive character with an IC50 as low as 33.28 ng mL −1 and 27.27 ng mL −1 for T‐2 and HT‐2, respectively. In addition, this method had no cross‐reaction with other structurally related mycotoxins. CONCLUSION: These results indicated that the developed CL‐ELISA could be applied for the detection of T‐2 toxin and HT‐2 toxin in actual samples without complicated steps. © 2016 Society of Chemical Industry